miRNAs as Biomarkers and Possible Therapeutic Strategies in Synovial Sarcoma - Jiang, Shaowei; Hu, Ying; Zhou, Yi; Tang, Guozheng; Cui, Wenxu; Wang, Xinyi; Chen, Bangjie; Hu, Zuhong; Xu, Bing (Frontiers in Pharmacology, 2022)
Synovial sarcoma (SS) is an epithelial-differentiated malignant stromal tumor that has the highest incidence in young people and can occur almost anywhere in the body. Many noncoding RNAs are involved in the occurrence, development, or pathogenesis of SS. In particular, the role of MicroRNAs (miRNAs) in SS is receiving increasing attention. MiRNA is a noncoding RNA abundant in cells and extracellular serums. Increasing evidence suggests that miRNA has played a significant role in the incidence and development of tumors in recent years, including sarcomas. Previous studies show that various sarcomas have their unique miRNA expression patterns and that various miRNA expression profiles can illustrate the classes of miRNAs that may elicit cancer-relevant activities in specific sarcoma subtypes. Furthermore, SS has been reported to have the most number of differentially expressed miRNAs, which indicated that miRNA is linked to SS. In fact, according to many publications, miRNAs have been shown to have a role in the development and appearance of SS in recent years, according to many publications. Since many studies showing that various miRNAs have a role in the development and appearance of SS in recent years have not been systematically summarized, we summarize the recent studies on the relationship between miRNA and SS in this review. For example, miR-494 promotes the development of SS via modulating cytokine gene expression. The role of miR-494-3p as a tumor suppressor is most likely linked to the CXCR4 (C-X-C chemokine receptor 4) regulator, although the exact mechanism is unknown. Our review aims to reveal in detail the potential biological value and clinical significance of miRNAs for SS and the potential clinical value brought by the association between SS and miRNAs.